2016
DOI: 10.1016/j.sleh.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep duration with kidney function and albuminuria: NHANES 2009-2012

Abstract: In a US representative sample of adults, self-reported short and long sleep duration were related to higher ACR. Short sleep duration was associated with higher eGFR and microalbuminuria. Research is needed to understand whether these associations indicate increased risk for kidney damage and cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 38 publications
0
29
0
3
Order By: Relevance
“…Based on sample size, these studies were also underpowered to assess the dose-response relationship. We found only one study that has investigated the association between sleep duration and glomerular hyperfiltration using a nationally representative sample in the United States [30]. In that study, the association differed by race-ethnicity, and long sleep duration was significantly related to glomerular hyperfiltration among Mexican Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Based on sample size, these studies were also underpowered to assess the dose-response relationship. We found only one study that has investigated the association between sleep duration and glomerular hyperfiltration using a nationally representative sample in the United States [30]. In that study, the association differed by race-ethnicity, and long sleep duration was significantly related to glomerular hyperfiltration among Mexican Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had investigated the association between sleep and kidney health outcome. Both short and long sleep duration were reported to be associated with decreased eGFR and the progression to ESRD among CKD 12, 21, 32, 33 or hypertension 18 population, and to be associated with increased eGFR, hyperfiltration, inadequate hydration and the prevalence of CKD among community-based general population 13, 19, 20, 2628 . In our study, based on same general community population, we further demonstrated that inappropriate sleep duration had converse effects on eGFR in healthy or early-stage nephropathy population, which was consistent to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies selected albuminuria as a terminal outcome to evaluate how sleep affects kidney function. Both short and long sleep duration had been reported to be associated with UACR level among populations from Japan 35 , Korea 36 and US 12 , and daytime napping had been reported to be positively associated with albuminuria in Japan 37 , however, this relationship is racial-specific 13 , whether it exists among Chinese population keeps unknown. This study confirmed the U-shaped relationship between sleep duration and albuminuria and the positive relationship between napping and albuminuria on the basis of the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations